PENDEKATAN STUDI ISLAM DITINJAU SECARA PSIKOLOGIS - Fauzan, Abas (Pascasarjana IAIN Kudus, 2013)
This article presents a review of psychological approaches to Islamic restrictions on potential solidify why people needreligion, the historical development of psychological approaches,characteristics, basic psychological approach and application ofpsychological approaches to life. Psychological approach has theduty to interpret how humans explore the religion and the religionof Islam, not just dwell on personal matters or just individuals, butalso about the review sentiments of individuals and groups withdifferent dynamics. The opinion of various tapers that psychologicalapproach is not aimed at assessing the level of a person’s religiousbut simply looks at how a person’s discover and understand religionas a guide in his life, so as to apply it to religious attitudes andbehaviors in daily life.